Identifying key parameters affecting the mechanical properties of 3D-printed ABS materials - Rizki, Muhammad Nuzan; Putra, Reza; Durmuş, Alpaslan; Isra, Muhammad (Jurnal Polimesin, 2025)
Advances in additive manufacturing (AM) technology have opened up opportunities for the rapid and precise production of complex components, including those used in unmanned aerial vehicle (UAV) structures. However, ABS material prints often exhibit variations in quality due to the influence of various interacting process parameters. This study aims to analyze the influence of four parameters: infill pattern, layer thickness, print speed, and chamber temperature on two important mechanical properties: ultimate tensile strength (UTS) and elongation. The Taguchi method with an experimental design using an orthogonal array L9(3⁴) was applied to minimize the number of trials without sacrificing important information. The tensile test data were analyzed using the signal-to-noise ratio (S/N ratio) and Analysis of Variance (ANOVA). The results showed that the infill pattern was the most dominant parameter, contributing 80.78% to UTS and 73.16% to elongation. Chamber temperature has a significant effect on elongation (19.78%), as it enhances interlayer bonding through temperature control in the printing chamber. Layer thickness contributes moderately to UTS (10.01%), while print speed has the smallest effect on both responses. These findings emphasize the importance of selecting the appropriate combination of parameters to consistently improve ABS print quality and serve as a foundation for developing process standards based on experimental data.